Improving bleaching results with hydrogen peroxide combined with desensitising agents for optimal aesthetic results: Meningkatkan hasil bleaching dengan hidrogen peroksida dikombinasikan dengan agen desensitisasi untuk hasil estetika yang optimal - Endo Sadewa; Juni Jekti Nugroho (Makassar Dental Journal PDGI Makassar, 2026)
Teeth whitening (bleaching) procedures are popular treatments due to increasing aesthetic demands. Hydrogen peroxide (H2O2) is the most commonly used agent in these procedures due to its clinically proven efficacy. The use of biomaterials such as gingival protectors and potassium nitrate-based desensitising agents has improved the safety profile of teeth whitening procedures. A 36-year-old woman presented to Hasanuddin University Hospital with the primary com-plaint of yellowing of her anterior teeth for approximately one year, seeking to improve her self-confidence. An in-office bleaching was performed using 40% H2O2 (Opalescence Boost), followed by the application of a gingival protectant (Opaldam-Ultradent) and the use of a potassium nitrate desensitising agent (Ul-traEZ) post-treatment. Hydrogen peroxide penetrates the enamel and releases free radicals that oxidise and break down the pigments causing stains into smaller, colourless molecules. The gingival protectant effectively prevents gingival irritation, while the desensitising agent relieves dentine sensitivity by depo-larising nerve endings and sealing dentine tubules. The external bleaching resulted in a significant colour change from 8 to 4. It was concluded that external bleaching treatment using 40% H?O? combined with protective measures for the gingival tissue effectively whitens teeth and achieves optimal results with minimal side effects.